Correlation-Based Task Scheduling Algorithm in Wireless Sensor Network - Fangfang Yan; Yue Shi; Wei Wei (Dianxin kexue, 2013)
There are some shortages of static scheduling algorithm（SCP）while scheduling tasks in wireless sensor network.A scheduling clustered tree was proposed，and a new clustering algorithm（ICS）based on task duplication was put forward. Compared with SCP’s experimental results，ICS doesn’t increase the completion time of tasks，while decreasing the number of needed node and the calculation of duplicated tasks and communication between different nodes，which achieve the purpose of reducing the network’s energy consumption.